Visual and Acoustic based Techniques for Motorcycle Collision Warning System with EEG Validation - MUZAMMEL, MUHAMMAD (2018)
In many countries, motorcyclist fatality rate is much higher than that of other vehicle drivers. Among many other factors, motorcycle rear-end collisions are also contributing to these biker fatalities. Collision detection systems can be used to minimize these fatalities. However, most of the existing collision detection systems do not identify the type of potential hazard faced by motorcyclists.